Canonical Mandel′shtam - Kahn, A (Open Book Publishers, 2017)
Mandel′shtam’s recognition as a premier Russian poet developed posthumously and largely outside the Soviet Union. The deepest record of engagement with his legacy lies in the world of Anglo-American letters, by writers and critics including Henry Gifford, Seamus Heaney, Geoffrey Hill, Robert Lowell, Donald Davie and Joseph Brodsky. This chapter analyses this material as evidence of why the history of Mandel′shtam’s reputation spheres has significant implications for how we think about the mechanisms of canon-formation and poetic afterlives. The specific development of Mandel′shtam studies, with its critical views on his poetic technique, and the question of his poetic difficulty, will feature only as a subsidiary treatment to the main narrative of reputation building. The larger tendencies that emerge as patterns in this reception emanate from convictions about poetry and the role of the poet. To a large degree, the story is part of the chapter of Russia abroad and the recovery of silenced voices in the diaspora.